Functional evidence for the inflammatory reflex in teleosts: A novel α7 nicotinic acetylcholine receptor modulates the macrophage response to dsRNA. (July 2018) - Torrealba, Débora; Balasch, Joan Carles; Criado, Manuel; Tort, Lluís; Mackenzie, Simon; Roher, Nerea
Abstract: The inflammatory reflex modulates the innate immune system, keeping in check the detrimental consequences of overstimulation. A key player controlling the inflammatory reflex is the alpha 7 acetylcholine receptor (α7nAChR). This receptor is one of the signalling molecules regulating cytokine expression in macrophages. In this study, we characterize a novel teleost α7nAChR. Protein sequence analysis shows a high degree of conservation with mammalian orthologs and trout α7nAChR has all the features and essential amino acids to form a fully functional receptor. We demonstrate that trout macrophages can bind α-bungarotoxin (α-BTX), a competitive antagonist for α7nAChRs. Moreover, nicotine stimulation produces a decrease in pro-inflammatory cytokine expression after stimulation with poly(I:C). These results suggest the presence of a functional α7nAChR in the macrophage plasma membrane. Further, in vivo injection of poly(I:C) induced an increase in serum ACh levels in rainbow trout. Our results manifest for the first time the functional conservation of the inflammatory reflex in teleosts. Highlights: Full-length and functional characterization of the rainbow trout α7nAChR. Trout macrophages bind α-bungarotoxin and nicotine stimulation competitively decreases α-bungarotoxin-binding in vitro. Nicotine modulates expression of mRNAs related to the immune response after stimulation with poly(I:C) in vitro. LPS and poly(I:C) are able to increase the expression of rainbow trout α7nAChR mRNA transcripts in vivo. LPS and poly(I:C) increase plasma and spleen acetylcholine levels in vivo.